A modelling approach to calculate economic and social benefits of resolving nautical bottlenecks on inland waterways - Bianca Duldner-Borca; Lisa-Maria Putz-Egger; Edwin van Hassel (European Transport Research Review)
Abstract Nautical bottlenecks, which occur when the fairway is insufficiently maintained, can significantly hinder the flow of goods and increase transportation costs. On the Danube to resolve nautical bottlenecks means to ensure a fairway depth of a minimum of 2.5 m throughout the year. Maintaining nautical bottlenecks is resource-intensive, nevertheless it brings benefits, for the shipping industry, the shippers and the whole society, i.e. environmental benefits. Our aim is to create a modelling approach to identify the extent of these benefits in monetary terms. Therefore, the goal of this paper is (1) to operationalize an already existing Key Performance Indicator (KPI)-framework by supplementing it with appropriate equations, which allows (2) developing a calculation model based on the operationalized KPI framework, which result in monetized economic and social benefits of resolving nautical bottlenecks and (3) testing it using a case study based on preliminary data from the Danube. On the one hand, the scientific community can build on this methodology and further develop it, e.g. by quantifying service level in IWT. On the other, policymakers gain first insights in the evaluation of removing nautical bottlenecks.